The association of modified QuEChERS and DLLME to offer high analytical detectability to assess residual depletion profile of erythromycin in fish - Campanharo, Sarah Chagas; da Silva, Agnaldo Fernando Baldo; Bleuzen, Anaïs; da Silva, Jonas Joaquim Mangabeira; de Freitas, Lucas Victor Pereira; Assane, Inácio Mateus [UNESP]; Pilarski, Fabiana [UNESP]; Paschoal, Jonas Augusto Rizzato (Elsevier, 2023)
An analytical method for the determination of erythromycin A (ERY) residues in fish fillet was developed, optimized, and validated employing a modified QuEChERS procedure associated to DLLME technique as a preconcentration step. The obtained LOD and the LOQ were 0.1 µg kg−1 and 1 µg kg−1, respectively. The validated method provides linearity in the range of 1 to 20 µg kg−1, precision (CV < 6.3 %) and accuracy (recovery ranging from 103 to 110 %). The procedure was applied in an experimental study to evaluate the residual depletion profile of ERY in fish (Piaractus mesopotamicus) after oral administration. The treatment was carried out at a daily dose of 100 mg (kg BW)-1 of ERY, for 7 consecutive days and with an average water temperature of 30 °C. A withdrawal time of 240°-day was estimated for eliminating ERY residues at concentration levels below the maximum residue limit considered (MRL 100 µg kg−1).
Keywords: Aquaculture; DLLME; Erythromycin; Food safety; QuEChERS; Veterinary drugs residues